Appropriate pre-transplant strategy for patients with myelodysplastic syndromes receiving allogeneic haematopoietic stem cell transplantation after myeloablative conditioning - Wang, Hong; Wang, Qingyuan; Qi, Jiaqian; Li, Xueqian; Chu, Tiantian; Qiu, Huiying; Fu, Chengcheng; Tang, Xiaowen; Ruan, Changgeng; Wu, Depei; Han, Yue (Frontiers in Immunology, 2023)
Purpose Appropriate pre-transplant strategies in patients with myelodysplastic syndromes (MDS) remain challenging. We sought to assess the effect of different pre-transplant therapies and transplantation interval times on patient prognosis. Methods We retrospectively analysed clinical data for 371 consecutive MDS patients after myeloablative transplantation between 2007 and 2019. Results The median age of the patients was 38 years (range, 12–64 years). A total of 114 patients (31%) received supportive care (SC), 108 (29%) hypomethylating agents (HMAs), and 149 (40%) chemotherapy-based therapy before transplantation. In patients who received HMA or SC, there was no significant difference in overall survival (OS; P=0.151) or relapse-free survival (RFS; P=0.330), except that HMA-treated patients had a lower rate of non-relapse mortality (5-year NRM: 18% vs. 32%, P=0.035). However, compared with patients who received HMA, those who received chemotherapy-based therapy had a lower 5-year OS rate (56% vs. 69%, P=0.020) and a slightly higher 5-year NRM rate (28% vs. 18%, P=0.067). Compared to the delayed transplant group (transplant interval ≥6 months), the early transplant group (transplant interval <6 months) had a superior 5-year OS (66% vs. 51%, P=0.001) and a lower 5-year cumulative incidence of NRM (22% vs. 36%, P=0.001). Conclusion The findings of the study indicate that receiving an appropriate pre-transplant strategy (SC/HMA + <6 months) significantly improves OS and decreases NRM in MDS patients after myeloablative transplantation.